Measurement of hepatic insulin sensitivity early after the bypass of the proximal small bowel in humans. (29th December 2016) - Miras, A. D.; Herring, R.; Vusirikala, A.; Shojaee‐Moradi, F.; Jackson, N. C.; Chandaria, S.; Jackson, S. N.; Goldstone, A. P.; Hakim, N.; Patel, A. G.; Umpleby, A. M.; Le Roux, C. W.
Summary: Objective: Unlike gastric banding or sleeve gastrectomy procedures, intestinal bypass procedures, Roux‐en‐Y gastric bypass in particular, lead to rapid improvements in glycaemia early after surgery. The bypass of the proximal small bowel may have weight loss and even caloric restriction‐independent glucose‐lowering properties on hepatic insulin sensitivity. In this first human mechanistic study, we examined this hypothesis by investigating the early effects of the duodeno‐jejunal bypass liner (DJBL; GI Dynamics, USA) on the hepatic insulin sensitivity by using the gold standard euglycaemic hyperinsulinaemic clamp methodology. Method: Seven patients with obesity underwent measurement of hepatic insulin sensitivity at baseline, 1 week after a low‐calorie liquid diet and after a further 1 week following insertion of the DJBL whilst on the same diet. Results: Duodeno‐jejunal bypass liner did not improve the insulin sensitivity of hepatic glucose production beyond the improvements achieved with caloric restriction. Conclusions: Caloric restriction may be the predominant driver of early increases in hepatic insulin sensitivity after the endoscopic bypass of the proximal small bowel. The same mechanism may be at play after Roux‐en‐Y gastric bypass and explain, at least in part, the rapid improvements in glycaemia.